Alkali/urea pretreatment of rice straw at low temperature for enhanced biological hydrogen production. (November 2018) - Dong, Lili; Cao, Guangli; Zhao, Lei; Liu, Bingfeng; Ren, Nanqi
Highlights: Cold alkali/urea pretreatment was employed to enhance H2 production from rice straw. Chemical compositions analysis revealed the efficiency of alkali/urea pretreatment. Cold NaOH/Urea pretreatment enabled a high energy conversion efficiency. This study provides a new promising way for enhanced H2 production from rice straw. Abstract: A pretreatment process using alkali/urea solution at low temperature was proposed for enhanced cellulosic biohydrogen production. Different alkaline solutions with both presence and absence of urea were studied. It can be found NaOH/Urea pretreatment exhibited excellent pretreatment performance at temperature from −8 °C to −20 °C. Microscopic structure observation combined FTIR analysis further demonstrated that NaOH/Urea pretreatment at low temperature could effectively disrupt the structure of rice straw and made more cellulose and hemicellulose available. The pretreated materials were then subjected for biohydrogen production by Thermoanaerobacterium thermosaccharolyticum M18. The maximum hydrogen production and energy conversion efficiency of 22.08 mmol/L and 9.76% were obtained from NaOH/Urea pretreated rice straw at low temperature. The results were 161.92% and 56.91% higher than the counterpart without pretreatment, respectively. This study provides a new direction to pretreat lignocellulose efficiently for enhanced biohydrogen production at cold climate region.